Sector Irradiation vs. Whole Brain Irradiation After Resection of Singular Brain Metastasis—A Prospective Randomized Monocentric Trial - Kerschbaumer, Johannes; Pinggera, Daniel; Holzner, Bernhard; Delazer, Margarete; Bodner, Thomas; Karner, Elfriede; Dostal, Lucie; Kvitsaridze, Irma; Minasch, Danijela; Thomé, Claudius; Seiz-Rosenhagen, Marcel; Nevinny-Stickel, Meinhard; et al. (Frontiers in Oncology, 2020)
To minimize recurrence following resection of a cerebral metastasis, whole-brain irradiation therapy (WBRT) has been established as the adjuvant standard of care. With prolonged overall survival in cancer patients, deleterious effects of WBRT gain relevance. Sector irradiation (SR) aims to spare uninvolved brain tissue by applying the irradiation to the resection cavity and the tumor bed. 40 were randomized to receive either WBRT (n=18) or SR (n=22) following resection of a singular brain metastasis. Local tumor control was satisfactory in both groups. Recurrence was observed earlier in the SR (median 3 months, 1-6) than in the WBRT cohort (median 8 months, 7-9) (HR 0.63; 95%CI 0.03-10.62). Seventeen patients experienced a distant intracranial recurrence. Most relapses (n=15) occurred in the SR cohort, whereas only two patients in the WBRT group had new distant tumor manifestation (HR 6.59; 95%CI 1.71-11.49; p=0.002). Median overall survival (OS) was 15.5 months (range: 1-61) with longer OS in the SR group (16 months, 1-61) than in the WBRT group (13 months, 3-52), without statistical significance (HR 0.55; 95%CI 0.69-3.64). Concerning neurocognition, patients in the SR group improved in the follow-up assessments, while this was not observed in the WBRT group. There were positive signals in terms of QOL within the SR group, but no significant differences in the global QLQ and QLQ-C30 summary scores were found. Our results indicate comparable efficacy of SR in terms of local control, with better maintenance of neurocognitive function. Unsurprisingly, more distant intracranial relapses occurred.